Novel Vesicular Formulation Based on a Herbal Extract Loaded with Niosomes and Evaluation of Its Antimicrobial and Anticancer Potential - Al-Enazi, Nouf M.; Alsamhary, Khawla; Ameen, Fuad; Nobre, Marcos Augusto Lima [UNESP] (MDPI, 2023)
This study aimed to enhance the anticancer and antibacterial properties of Pistacia atlantica through a new parenteral formulation. The innovative approach involved loading P. atlantica fruit extract onto a novel Pluronic vesicular nano platform (Nio), analyzed using various techniques like GC-Mass, SEM, DLS, and UV-vis. The results revealed a stable, spherical Nio/Extract formulation of 103 ± 4.1 nm, possessing a high zeta potential of −30 ± 2.3 mV, with an impressive encapsulation efficiency of nearly 90 ± 3.5%. This formulation exhibited heightened cytotoxicity against BT-20 and MCF-10 cell lines compared to the extract alone, indicating its potential as a drug carrier with prolonged release characteristics. Additionally, the Nio/Extract demonstrated superior antibacterial effects against Pseudomonas aeruginosa, Staphylococcus epidermidis, and Candida albicans compared to the free extract, showcasing MIC values of 211, 147, and 187 ug/mL, respectively, versus 880, 920, and 960 ug/mL for the pathogens. These findings highlight the potential of niosomal nano-carriers housing P. atlantica extract as a viable therapeutic strategy for combating both malignancies and microbial infections.
Keywords: anticancer; antimicrobial; Green Synthesize; Herbal Extract; niosome; vesicular formulation